Trends in emergency contraception awareness among women and girls in 28 sub-Saharan countries - Oluwafemi Emmanuel Awopegba; Okechukwu Stephen Chukwudeh; Eyitayo Omolara Owolabi; Anthony Idowu Ajayi (BMC, 2021)
Abstract Background Studies have shown that emergency contraception (EC) remains underutilised in preventing unintended pregnancy in sub-Saharan Africa (SSA). Small-scale surveys have attributed EC underutilisation to gaps in EC awareness among SSA women and girls. However, limited studies have explored trends in EC awareness in SSA. We address this gap by examining trends in EC awareness using data from 28 SSA countries. Our analysis was disaggregated by age distribution, place of residence, level of education, and wealth to show differences in EC awareness trend. Methods We analysed the Demographic and Health Surveys (DHS) data of 1,030,029 women aged 15 to 49 on emergency contraception awareness. EC awareness was defined as having ever heard of special pills to prevent pregnancy within 3 days after unprotected sexual intercourse. Frequencies and percentages were used to summarise trends in EC awareness between years 2000 and 2019. Results Overall, there was an upward shift in the level of EC awareness in all countries, except in Burkina Faso, Niger, Chad, and Ethiopia. While some countries recorded a significant upward trend in EC awareness, others recorded just a slight increase. Women in Kenya, Ghana, Gabon, and Cameroon had the highest upward shift in EC awareness. For example, only 28% of women were aware of EC in Ghana in 2003, but in 2014, 64% of women knew about EC, an increase of over 36 percentage points. Increase in EC awareness was starker among women aged 20-24 years, those who resided in urban areas, had higher education, and belong to the highest wealth quintile, than those aged 15-19, in rural areas, with no formal education and belonging to the lowest wealth quintile. Conclusion Our analysis shows that the level of EC awareness has increased substantially in most SSA countries. However, EC awareness still differs widely within and between SSA countries. Intervention to improve EC awareness should focus on women aged 15 to 19, those with no formal education, residing in rural areas, and within the lowest quintile, especially, in countries such as Chad, Niger, Burkina Faso, and Ethiopia where level of EC is low with lagging progress.